Knowledge mapping of the research on lexical inferencing: A bibliometric analysis - Yang, Hui; Fan, Lin; Yin, Hongshan (Frontiers in Psychology, 2023)
Lexical inferencing functions as one of the most important and effective skills used in language comprehension pertaining to psychological, cognitive and neurological aspects. Given its complex nature and crucial role in language comprehension, lexical inferencing has received considerable attention. The present study visualized the knowledge domain of the research on lexical inferencing based on a total of 472 articles collected from Web of Science (WoS) Core Collection of Thomson Reuters from 2001 to 2021. The bibliographic data were analyzed through co-cited articles, co-citation clusters of references and co-occurring terms to identify holistic intellectual landscape of lexical inferencing with special focus on its intellectual structure and base, and hot research topics. The main intellectual base includes probability of activating lexical inferencing in working memory and encoding in long-term memory, the role of lexical inferencing in reading comprehension, in connected speech, in children’s derivation under pragmatic context, and in psychological and neurocognitive processes underlying language processing mechanism. Hot topics are comprised of the impacts of lexical inferencing on language acquisition and comprehension (written and spoken language comprehension), the factors (context variables, vocabulary knowledge, morphological awareness) affecting the presence and efficacy of lexical inferencing, and time course of lexical inferencing during reading. Critically, the results of this study demonstrated the contribution of lexical inferencing to language comprehension was strongly correlated with learner-related and discourse-related variables. The study shed valuable light on the understanding of the intellectual background and the dynamic patterns of lexical inferencing over the past two decades, thereby future work in lexical inferencing is suggested as well.